Reduction Of Iron And Mica Content In Silica Sand From Terengganu Silica Consortium Sdn Bhd By Attrition Scrubbing - Zali, Muhammad Zulkif Mat (Universiti Sains Malaysia, 2017)
In this study, the characterization and processing of silica sand was done using attrition scrubbing method. The aim of this study is to upgrade the silica sand from Terengganu Silica Consortium Sdn Bhd by reducing the iron and mica content using attrition scrubbing method. Hence, the characterization of the silica sand sample before attrition scrubbing process were carried out at the initial stage of the investigation. This initial stage were included the particle size distribution analysis, loss on ignition (L.O.I), X-ray Diffraction (XRD), X-ray Fluorescence (XRF), optical microscope observation and Scanning Electron Microscope with Energy-dispersive X-ray Spectroscopy (SEM-EDX). This characterization results determined the contaminated minerals in the silica sand which are iron stains, feldspar, mica, tourmaline and amphibole. This results also will be used to compare the mineral properties in the silica sand before and after scrubbing process. For this purpose, the operational parameters of attrition scrubbing process, namely solid percent, rotor speed, scrubbing time and pH condition were manipulated to observe their effects on the silica concentration. This test were carried out at neutral, acidic and alkali condition with varies of time. From XRF analysis results, it found that the grade of silica sand was increased from 97.97% to about 99.22% after the attrition scrubbing process. From this analysis, it was found that the scrubbing time and pH condition had significant effect on the separation. Thus, this removal of contaminated mineral is very essential to ensure the high quality of silica sand can be produced for the glass manufacture.